PTH-006 Complexity of polyps identified via bowel screening programme in NHS greater glasgow and clyde. (June 2019) - Berriman, Thomas; Brownson, Emily; Pace, Lynn; Morris, Judith; Winter, Jack Westwood
Abstract : Introduction: Colonic polyps are a common finding in the bowel screening colonoscopy program (BCSP). Standard practice is to remove at index colonoscopy if possible. The SMSA polyp scoring system is a method of scoring the difficulty of polypectomy and is not currently recorded in routine practice in our institution. We wished to prospectively audit the spread of SMSA scores in polyps identified in BCSP colonoscopy in NHS Greater Glasgow and Clyde (GGC). Knowledge of the frequency of higher SMSA scores will allow resource planning for the volume of cases which need to be undertaken by an expert endoscopist. We also anticipated the exercise would be formative to our cohort of BCSP colonoscopists when assessing adenoma complexity. Methods: NHS GGC features 8 endoscopy units with BCSP colonoscopy performed at all sites. Between 1st November 2017 and 28th February 2018 we prospectively audited the spread of complexity of adenomas detected on bowel screening colonoscopy. We recorded SMSA polyp characteristics, endoscopic techniques used and the deferral rate and reason. Results: 626 records of polyp assessment were returned. 149 were excluded (outwith date window, invalid CHI, non-BCSP colonoscopy indication). 477 polyps were therefore included in the audit, from a total of 207 BCSP endoscopies. This cohort comprised approximately 30% of bowel screening colonoscopies undertaken during that time period. 16 Colonoscopists performed BCSP colonoscopy in the studied time-frame: 1 nurse endoscopist, 2 gastroenterologists, 13 colorectal surgeons. The range of SMSA Scores for polyps was 4–17 (Median 6). 174 (36.5%) were level 1 polyps, 259 (54.3%) were level 2 polyps, 32 (6.7%) were level 3 polyps and 7 (1.5%) were level 4 polyps. 457 Polyps were removed at index colonoscopy (96%). Polypectomy deferral rates varied by SMSA level: 42.9% (3 of 7) for SMSA Level 4 polyps, 18.8% (6 of 32) for SMSA level 3 polyps, 1.5% ( 2 of 259) for level 2 polyps, and 4% (7 of 174) for level 1 polyps. The commonest reason for deferring level 1 and 2 polyps was failure to stop the patient's anticoagulant or antiplatelet medication. Conclusion: 8.2% of polyps detected on bowel screening colonoscopy were SMSA level 3 and 4. The majority of these were removed at index colonoscopy. It is uncertain whether removal at index procedure was uniformly the correct approach in patients with level 3 and 4 polyps and we require to do further research looking at completeness of excision. This audit was undertaken when Guaic based faecal testing was being utilised by the bowel screening programme. Since the change to Faecal Immunochemical Test with a threshold of 80ug/g stool we have seen an increase in adenoma detection rates from 40% to 52% and therefore the spread of SMSA scores may have changed.